Popular Education and University Outreach in Food and Nutrition Security and the Human Right to Adequate and Healthy Food: a possible methodological path - Beatriz Oliveira Blackman Machado; Anelise Rizzolo de Oliveira (Universidade do Estado do Rio de Janeiro, 2020)
Introduction: The theme of food and nutrition security and the human right to adequate and healthy food became a political issue in Brazil, from 2003 to 2016. However, the task of maintaining social rights was not completed and today it is politically threatened, demanding the consciousness and mobilization of segments of civil society for an understanding of reality and the resumption of the construction of possible paths for the enforceability of the law and guarantee of food and nutritional security. Objective: This work sought to report the experience and highlight the pedagogical expressions of the principles of popular education throughout the teaching-learning process of the 2018 edition of the course, held in the municipality of Colinas do Sul, Goiás. Methods: At the University of Brasília, in 2018, an Outreach and Continuing Education Program, MultiplicaSAN, was instituted. Among its activities, there was a course to promote the culture of rights aiming at the formation of civil society in the themes of food and nutritional security and the human right to adequate and healthy food, using Freire's pedagogy and the principles of Popular Education Policy. Results: The experience of the outreach program provided an in-depth look at popular education, showing the wealth of knowledge construction together with a community of female workers. Conclusion: It also revealed the transformative potential of an educational process based on the principles of popular education: lovingness, dialogicity, consciousness, construction of knowledge, based on concrete reality, transformation of the world and systematization of knowledge in the teaching-learning process of educators and students.